Effect of Biochar from Urban Waste and Eco-enzymes on Growth and Yield of Shallots (Allium ascalonicum, L) - Elisabet Restiana Jaya; Yohanes Parlindungan Situmeang; Anak Agung Sagung Putri Risa Andriani (SEAS (Sustainable Environment Agricultural Science), 2021)
Abstract This study aims to determine the effect of biochar dose from urban waste and the concentration of eco-enzymes and their interactions on the growth and yield of shallots. The research was carried out in the greenhouse of the Faculty of Agriculture,Warmadewa University with an altitude of 25 m above sea level, and took place from April to June 2021. This study used a factorial randomized block design method consisting of two factors. The first factor is the dose of biochar with 4 levels (0; 5; 10; and 15 tons ha-1), while the second factor is the concentration of eco-enzyme which consists of 4 treatment levels (0; 7.5; 15.0; and 22.5 ml l-1). The results showed that the interaction between the dose of biochar and the concentration of eco-enzyme had a significant effect on the fresh weight of the stover per clump and had a very significant effect on the dry weight of the stover per clump, but had no significant effect on other variables. The treatment dose of biochar and eco-enzyme had a very significant effect on all observed variables. The results showed that the biochar and eco-enzyme treatments had a very significant effect on all observed variables. The application of biochar and eco-enzyme has a very significant effect on all observed variables. The provision of biochar treatment from urban waste was able to increase the fresh weight of tubers in the 15-ton ha-1 treatment, which was an increase of 39.40% compared to without biochar, while the highest fresh fruit weight was obtained in the eco-enzyme treatment of 22.5 ml l-1, which increased by 29.77% compared without eco-enzyme. Keywords: Biochar; urban waste; eco-enzyme; shallots